Connecting Family Protocol and Family Council to Perceived Succession Success in Family Businesses through Management Succession Planning - Guntoro, Jennifer Alberta; Yusup, Adi Kurniawan (Management Analysis Journal, 2025)
The aim of the research is to identify the effect of family protocol and family council toward perceived success of succession though management succession planning mediation.   Family business refers to a corporation that has been controlled and owned by the same family for generations. Exercising rational business decisions while also managing the interpersonal dynamics of a family-owned enterprise is a challenging task. Achieving equilibrium between the expectations and fluctuations of family members and the company's enduring objectives is frequently imperative in this situation. The analysis conducted using quantitative analysis. The population of the research is family business successor at Surabaya. The sampling method used is purposive sampling. The respondent participated in this research is 120 respondents. The data analysed using Partial Least Square Method using SmartPLS application. The data analysis showed that family protocol and family council positively affect management succession planning. In addition, family council, family protocol, and management succession planning directly affect perceived success of succession. The finding also discovered that management succession planning also successfully mediated the relationship between family council and family protocol toward perceived success of succession.